Safety and efficacy of depatuxizumab mafodotin + temozolomide in patients with EGFR-amplified, recurrent glioblastoma: results from an international phase I multicenter trial. Issue 1 (5th July 2018) - Lassman, Andrew B; van den Bent, Martin J; Gan, Hui K; Reardon, David A; Kumthekar, Priya; Butowski, Nicholas; Lwin, Zarnie; Mikkelsen, Tom; Nabors, Louis B; Papadopoulos, Kyriakos P; Penas-Prado, Marta; Simes, John; et al.
Abstract: Background: Patients with glioblastoma (GBM) have a dismal prognosis. Nearly all will relapse with no clear standard of care for recurrent disease (rGBM). Approximately 50% of patients have tumors harboring epidermal growth factor receptor ( EGFR ) amplification. The antibody–drug conjugate depatuxizumab mafodotin (depatux-m) binds cells with EGFR amplification, is internalized, and releases a microtubule toxin, killing the cell. Here we report efficacy, safety and pharmacokinetics (PK) of depatux-m + temozolomide (TMZ) in patients with EGFR -amplified rGBM. Methods: M12-356 (NCT01800695) was an open-label study encompassing patients with newly diagnosed or rGBM across 3 treatment arms. Results are reported for adults with EGFR -amplified, measurable rGBM who received depatux-m (0.5–1.5 mg/kg) on days 1 and 15, and TMZ (150–200 mg/m 2 ) on days 1–5 in a 28-day cycle. Patients were bevacizumab and nitrosourea naïve. Results: There were 60 patients, median age 56 years (range, 20–79). Fifty-nine patients previously received TMZ. Common adverse events (AEs) were blurred vision (63%), fatigue (38%), and photophobia (35%). Grades 3/4 AEs were split between ocular and non-ocular AEs, occurring in 22% of patients each. Systemic PK exposure of depatux-m was dose proportional. The objective response rate was 14.3%, the 6-month progression-free survival rate was 25.2%, and the 6-month overall survival rate was 69.1%. Conclusions: Depatux-m + TMZ displayed an AE profile similar to what was described previously. Antitumor activity in this TMZ-refractory population was encouraging. Continued study of depatux-m in patients with EGFR -amplified, newly diagnosed, or recurrent GBM is ongoing in 2 global, randomized trials (NCT02573324, NCT02343406).